A J-Shaped Curve Relationship Between Baseline Fasting Blood Glucose and 1-Year Stroke Recurrence in Non-diabetic Patients With Acute Cerebral Infarction in Xi'an, China: A Multicenter Observational Cohort Study - Liu, Zhongzhong; Lin, Xuemei; Lin, Wenjuan; Lu, Qingli; Liu, Pei; Wang, Jing; Liu, Yan; Chang, Qiaoqiao; Wang, Yan; Song, Chensheng; Wang, Fang; Shi, Yaling; et al. (Frontiers in Neurology, 2022)
Background: The relationship between baseline fasting blood glucose (FBG) levels and 1-year stroke recurrence in non-diabetic patients with acute cerebral infarction (ACI) is unclear. We aimed to clarify this relationship in non-diabetic patients with ACI. Methods: Baseline FBG levels and related information of the patients were collected at admission and the events of stroke recurrence were followed up 1, 3, 6 and 12 months after the patients were discharged. Baseline FBG levels were analyzed as continuous variables and quartiles (Q1-Q4). Multivariate Cox regression models and a two-piecewise linear regression model were used to investigate the relationship and determine the threshold effect between baseline FBG levels and 1-year stroke recurrence in non-diabetic ACI patients. Results: Overall, 1634 non-diabetic patients with ACI were enrolled. After adjusting for potential confounding factors, the hazard is 2.24-fold higher in Q4 than those in Q2, being considered the reference in non-diabetic patients with ACI (hazard ratio [HR]=2.24, 95%CI: 1.08-4.65, P=0.031). Plotting hazard ratios over baseline FBG levels suggested a J-shaped relationship for 1-year stroke recurrence. Further analysis revealed that the nadir value of baseline FBG levels is 4.6 mmol/L. The relationship was more significant in patients with atrial fibrillation than in those without (P for interaction=0.009). Conclusions Lower and higher baseline FBG levels may lead to an increased risk of 1-year stroke recurrence in non-diabetic patients with ACI as shown by a J-shaped curve with a nadir value of 4.6 mmol/L.